(untitled) (International Journal of Nursing Education, 2019)
Hypertension is a common disease associated with high morbidity and mortality. The disease is a silent threat to the health of people all over the world. Thus, early detection of hypertension and its precipitating or aggravating factors are important if one is to evolve measures so that complications of hypertension can be prevented. On the other hand obesity is a major health problem that affecting women mostly. Obesity has become one of our nation’s leading epidemics. According to the Centre for Disease Control (CDC) obesity has almost tripled over the past 30 years. Obesity is strongly associated with hypertension and cardiovascular disease. Obesity is also associated with endothelial dysfunction and renal functional abnormalities that may play a role in the development of hypertension. The continuing discovery of mechanisms regulating appetite and metabolism is likely to lead to new therapies for obesity-induced hypertension. Methodology: A non-experimental approach with simple random sampling technique was used in the study. The data was collected through body mass index scoring sheet, assessment sheet for hypertension and health assessment Performa. The final study was also conducted on 200 women in selected area of Punjab. Descriptive and inferential statistics were employed to analyze the data. Result: The results showed that out of 200 subjects 42.5% were overweight. 30.5% subjects comes under pre hypertension, 16% subject comes under stage- I hypertension while only 3% subjects comes under stage –II hypertension category. The findings revealed that there was a significant association between hypertension with demographic variable like age, education, duration of hypertension, type of family and life style and not any significant association between hypertension and demographic variables such as occupation, religion, marital status, family history of hypertension, family history of obesity, income (monthly) and dietary pattern. There was a significant association between obesity with demographic variable like marital status, duration of hypertension and life style and not any significant association between obesity and demographic variables such as Age, education, occupation, religion, family history of hypertension, family history of obesity, income (monthly), type of family and dietary pattern.